2017
DOI: 10.2147/dmso.s143046
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and unmet needs in basal insulin therapy: lessons from the Asian experience

Abstract: Basal insulin therapy can improve glycemic control in people with type 2 diabetes. However, timely initiation, optimal titration, and proper adherence to prescribed basal insulin regimens are necessary to achieve optimal glycemic control. Even so, glycemic control may remain suboptimal in a significant proportion of patients. Unique circumstances in Asia (eg, limited resources, management of diabetes primarily in nonspecialist settings, and patient populations that are predominantly less educated) coupled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 64 publications
(102 reference statements)
0
40
0
Order By: Relevance
“…Studies indicate that the rate of hospitalizations and mortality is higher in nonadherent patients with T2DM than in adherent patients. Also, significantly higher HbA1c levels were observed in patients with T2DM who missed insulin injections compared with those who never missed a dose [29].…”
Section: The Insulin Conversationmentioning
confidence: 93%
See 3 more Smart Citations
“…Studies indicate that the rate of hospitalizations and mortality is higher in nonadherent patients with T2DM than in adherent patients. Also, significantly higher HbA1c levels were observed in patients with T2DM who missed insulin injections compared with those who never missed a dose [29].…”
Section: The Insulin Conversationmentioning
confidence: 93%
“…• Delay in Initiation of Insulin Therapy: Delay in initiating insulin therapy has been a major challenge in real-world clinical practice. Many Asian and international studies have shown that even when there was no significant improvement in glycemic control, initialization of insulin therapy was always delayed [29]. • Insufficient Dose Titration: Timely initiation of insulin therapy is not the only factor that provides optimal glycemic control.…”
Section: The Insulin Conversationmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin degludec has been available in Thailand since October 2016. Although the clinical trial results revealed less nocturnal hypoglycemia, the data from real-world settings is limited especially in Asian patients [11,12]. To gain further knowledge on clinical effectiveness, treatment patterns, satisfaction with new insulin treatment and quality of life (QOL) among Thai patients with diabetes (both T1DM and T2DM) initiating insulin degludec in a real-life clinical setting, we conducted a 12-month, prospective non-interventional study in a single specialized diabetes center in Bangkok, Thailand.…”
Section: Introductionmentioning
confidence: 99%